Structural Relationships Between Cognitive Function, Depressive Symptoms, Self-Care Confidence, and Maintenance in Patients With Heart Failure - JinShil Kim RN, PhD, FAHA, FAAN; Seon Young Hwang RN, PhD, FAHA; Sun Hwa Kim RN, PhD; Jae Lan Shim RN, PhD (SAGE Publishing, 2023)
Introduction In order to promote self-care maintenance behavior in patients with heart failure (HF), it is necessary to identify the direct and indirect effects of major latent variables. Objective This study aimed to identify structural relationships between different domains of cognitive function, depression and self-care confidence, and self-care maintenance. Methods This descriptive study involved a secondary analysis using data of 201 patients with HF from two observational studies in three hospitals in Korea. The structural equation model using AMOS version 24.0 was constructed to assess the relationships among the variables. The Seoul Neuropsychological Screening Battery was used to assess global cognition, immediate/delayed memory, and executive function, and the Self-Care of HF Index v.6.2. was used for self-care confidence and maintenance. Results Self-care maintenance was affected by memory function with a significant direct effect (β=.43, p  = .006), as well as self-care confidence (β=.70, p  < .001). Memory function and global function indirectly affected self-care maintenance through self-care confidence (β = −.37, p  = .002; β = .14, p  = .030). Depressive symptoms also had an indirect effect through self-care confidence on self-care maintenance (β = −.21, p  = .005). Conclusion This study confirmed that it is important to increase self-care confidence through supportive care and to maintain memory function for maintaining self-care in the chronic course of HF patients. In particular, this study suggests that it is necessary to perform periodic memory check-ups for chronic HF patients on an outpatient basis, and counseling and education are needed to improve memory and increase confidence in self-care.